Clinical Evaluation of a Self-Adhering Flowable Resin Composite in Minimally Invasive Class I Cavities: 5-year Results of a Double Blind Randomized, Controlled Clinical Trial - Fatma Dilsad Oz; Esra Ergin; Filiz Yalcin Cakir; Sevil Gurgan (University of Zagreb. School of Dental Medicine, 2020)
Objective: The aim of this study was to evaluate the long-term clinical performance of a self-adhering flowable resin composite compared to a conventional flowable resin composite used with an etch&rinse adhesive system in minimally invasive Class I cavities. Materials and Methods: Twenty-five patients received at least one pair of Class I restorations (n=65). After Class I cavities had been prepared, they were randomly restored either with a self-adhering flowable resin composite (Vertise-Flow/Kerr-VR) [Group-1 (n=33)], or with a flowable resin composite (Luxaflow/DMG-LX) in combination with an etch&rinse adhesive (Teco/DMG) [Group-2 (n=32)] according to the manufacturers' instructions. The restorations were evaluated at baseline and yearly during 5 years according to the FDI criteria by two evaluators. A statistical analysis was carried out using the Pearson Chi-Square test and the Cochran Q-test followed by the Mc Nemar's test (p=0.05). Results: After 5 years a total of 47 restorations were evaluated with a recall rate of 68%. At 4-year, 3 (11.5%) VR and 2 LX (7.6%) restorations exhibited a cumulative retention loss. Seventeen (73.9%) VR and 14 LX (58.3%) restorations exhibited clinically acceptable (2) scores for marginal adaptation. At 5-year evaluations VR and LX showed similar results regarding all evaluated criteria (p > 0.05). The cumulative retention loss rates of VR and LX were 15.3% and 7.6%, respectively. None of the restorations demonstrated a recurrence of caries and post operative sensitivity. Both materials showed significant changes at 4 and 5 years regarding marginal staining when compared to baseline (p<0.001). Furthermore, significant changes were observed for VR and LX at 1, 2, 3, 4 and 5 years for marginal adaptation according to baseline (p<0.001). Conclusion: The use of both materials for the restoration of Class-I cavities demonstrated clinically acceptable performance at the end of 5-year. The self-adhering flowable composite exhibited a clinical performance similar to the conventional flowable applied with an etch&rinse adhesive.